2018
DOI: 10.3390/toxins10120492
|View full text |Cite
|
Sign up to set email alerts
|

Resistance-Related l-Pyroglutamic Acid Affects the Biosynthesis of Trichothecenes and Phenylpropanoids by F. graminearum Sensu Stricto

Abstract: Fungicide application remains amongst the most widely used methods of fungal control in agroecosystems. However, the extensive use of fungicides poses hazards to human health and the natural environment and does not always ensure the effective decrease of mycotoxins in food and feed. Nowadays, the rising threat from mycotoxin contamination of staple foods has stimulated efforts in developing alternative strategies to control plant pathogenic fungi. A substantial effort is focused on the identification of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In the present study, we identified the optimum growth parameter of L. plantarum against several biotic and abiotic stress conditions, grew the bacteria under such conditions and utilized the cell-free metabolome for cell-based assays. Among the highly abundant metabolites, the antioxidant effects of 5-oxoproline (aka pyroglutamic acid) [ 27 ], butanedioic acid (i.e., succinic acid) [ 28 ], N , N -dimethylglycine [ 29 ], etc. have already been established.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified the optimum growth parameter of L. plantarum against several biotic and abiotic stress conditions, grew the bacteria under such conditions and utilized the cell-free metabolome for cell-based assays. Among the highly abundant metabolites, the antioxidant effects of 5-oxoproline (aka pyroglutamic acid) [ 27 ], butanedioic acid (i.e., succinic acid) [ 28 ], N , N -dimethylglycine [ 29 ], etc. have already been established.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation revealed that the synthetic L-pyroglutamic acid analogs have been proved to be novel fungicide candidates to fight F. solani and G. candidum, two strains that are known to pose health risks related to major barrier breaks among people with weak immune systems [8]. Previous studies stated that the application of pyroglutamic acid and its derivatives is capable of increasing lettuce yield [9], conferring protection to bread wheat against Zymoseptoria tritici [7], affecting the biosynthesis of trichothecenes and phenylpropanoids [10] stimulating DNA synthesis in rat primary hepatocytes [11], showing anti-HIV-1 and anti-HCV activity [12], exhibiting antioxidant activity and anti-inflammatory activity [13], showing selective Gram-negative antibacterial activity and antiplatelet activity [14,15], and acting as a new farnesyl transferase inhibitor [16]. In our previous research, it was found that L-pyroglutamic acid extracted from Disporopsis Aspera Engl.…”
mentioning
confidence: 99%